Clinical epidemiology of septic arthritis caused by Burkholderia pseudomallei and other bacterial pathogens in northeast Thailand - Teparrukkul, P; Nilsakul, J; Dunachie, S; Limmathurotsakul, D (American Society of Tropical Medicine and Hygiene, 2017)
Septic arthritis is a medical emergency, and if not treated appropriately, it can be associated with high morbidity and mortality. Melioidosis, a serious infectious disease caused by the Gram-negative bacillus Burkholderia pseudomallei, is highly endemic in South and Southeast Asia and northern Australia. We reviewed the medical charts of adult patients admitted with bacterial septic arthritis at Sunpasitthiprasong Hospital, Ubon Ratchathani, northeast Thailand from January 2012 to December 2014. Bacterial septic arthritis was defined as one or more hot swollen joints with isolation of a pathogenic organism from an affected joint or from blood. A total of 154 patients with septic arthritis were retrospectively evaluated. The most common causes were B. pseudomallei (48%, N = 74), Streptococcus spp. (29%, N = 44), and Staphylococcus aureus (10%, N = 16). Prevalence of diabetes, bacteremia, and pneumonia was higher in B. pseudomallei septic arthritis than in septic arthritis caused by the other bacteria (all P < 0.01). Seventy three percent (54/74) of patients infected with B. pseudomallei and 69% (55/80) of patients with the other bacteria received effective antimicrobials on the first day of admission (P = 0.60), but in-hospital mortality of the former group was considerably higher (34% versus 14%, P = 0.004). In conclusion, B. pseudomallei septic arthritis is common and associated with high mortality in northeast Thailand. Emergence of Streptococcus arthritis is observed. Difficulty in diagnosing melioidosis and identifying B. pseudomallei in areas where health care workers are not familiar with the disease is discussed. In melioidosis-endemic regions, parenteral ceftazidime could be considered as empirical antimicrobial therapy for patients with septic arthritis and underlying diseases.